Religion as a Source of Legitimacy: Analyzing the Role of Religion in Political Power Across Cultures - Setiawan Setiawan; Muhammad Hatta; Alhuda Alhuda; Darmadi Darmadi (Electronic Journal of Education, Social Economics and Technology, 2025)
Religion, which serves as a system of social beliefs and norms, is often used by leaders to acquire and maintain power. The study shows that legitimacy gained through religion can strengthen political control, as seen in the Iranian context after the 1979 Islamic Revolution. On the other hand, religion is also a tool for mass mobilization in social movements, such as Action 212 in Indonesia. While religion can strengthen social solidarity, it also has the potential to spark conflict, especially when associated with national identity, as in India. Qualitative methods are used to examine the complex relationship between religion and politics, including the influence of religious values in policymaking. The findings suggest that the relationship between religion and politics is dynamic, and can serve as a source of stability or conflict, depending on the existing social and cultural context.